Diversion of Juvenile Criminal Cases at the Investigation Stage at the Ternate City Police Force - Fahria; M. Djafar, Muhammad Mufti; Budiono, Arief; Ikrima, Nur Aida (Dinasti Research, 2025)
Diversion of juvenile criminal cases at the investigation stage at the Ternate City Police Force. Object: This research analyzes the diversion of child molestation cases at Ternate Police Force during the investigation stage. Objective: This paper analyzes: (1) the diversion implementation of at the investigation stage of child molestation crimes at the Ternate Police Force and (2) the factors that influence the implementation of diversion at the investigation stage of child molestation crimes. Method: This research used empirical research, which is a research model in the form of an action to observe a legal reality in society. Results: At the investigation stage, diversion implementation at the crime of child molestation cannot be carried out because according to Article 7 clause (2) of Law No. 11 of 2012, diversion can only be carried out on children who commit crimes with a prison sentence of less than seven years and are not a repeat of the crime. However, the Ternate City Police Force provides a solution of mediation. Factors that influence the implementation of diversion at the investigation stage of child molestation crimes include an obstacle where the victim's family prefers to continue the legal process rather than mediate.